Acute Management of Optic Neuritis: An Evolving Paradigm. Issue 3 (September 2018) - Horton, Lindsay; Bennett, Jeffrey L.
Abstract : Abstract: The current management of acute optic neuritis (ON) is focused on expediting visual recovery through the use of high-dose intravenous corticosteroids. The recent identification of specific autoantibodies associated with central nervous system inflammatory disorders has provided novel insights into immune targets and mechanisms that impact the prognosis, treatment, and recurrence of ON. Therefore, neurologists and ophthalmologists need to be aware of clinical, laboratory, and imaging findings that may provide important clues to the etiology of ON and the potential need for aggressive management. Moving forward, rapid and accurate diagnosis of inflammatory ON will likely be critical for implementing clinical care that optimizes short-term and long-term therapeutic outcomes.